Alien legalization program ; Political parties ; Viajes Filipinos [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1988)
The CID proposes a scheme for aliens wishing to have permanent status in the Philippines. The proposal was disapproved in the Senate. Takes a look at Philippines political parties and their platforms. A tour to the homes of Filipino artists, fisherfolk in the Laguna area and the those of the wood carving artisans.
Alien legalization (15 min.) -- Political parties (18 min.) -- Viajes Filipinas (9 min.)
VHS.
Keywords: Manansala, Vicente, 1910.; Illegal aliens -- Philippines; Political parties -- Philippines; Art museums -- Philippines; Philippines -- Emigration and immigration